2009
DOI: 10.1109/tgrs.2009.2029340
|View full text |Cite
|
Sign up to set email alerts
|

Decision Fusion for the Classification of Hyperspectral Data: Outcome of the 2008 GRS-S Data Fusion Contest

Abstract: Abstract-The 2008 Data Fusion Contest organized by the IEEE Geoscience and Remote Sensing Data Fusion TechnicalCommittee deals with the classification of high-resolution hyperspectral data from an urban area. Unlike in the previous issues of the contest, the goal was not only to identify the best algorithm but also to provide a collaborative effort: The decision fusion of the best individual algorithms was aiming at further improving the classification performances, and the best algorithms were ranked accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
75
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(81 citation statements)
references
References 23 publications
(23 reference statements)
2
75
0
4
Order By: Relevance
“…Moreover, nonlinear relationships can be accounted for due to the kernel trick. SVMs are now widely used in the field of remote sensing not only for the purpose of hyperspectral image processing [12] but also for continuous variable estimation [10], [13]- [16].…”
mentioning
confidence: 99%
“…Moreover, nonlinear relationships can be accounted for due to the kernel trick. SVMs are now widely used in the field of remote sensing not only for the purpose of hyperspectral image processing [12] but also for continuous variable estimation [10], [13]- [16].…”
mentioning
confidence: 99%
“…22 The overall result showed that SVM classification process employed has got very promising potential to discriminate crops and tree classes, with high classification accuracies, when combined with high spectral resolution hyperspectral remote sensing data. The high accuracy produced by the SVM classifier may be due to the ability of the algorithm to identify the optimally separating hyperplanes for classes in comparison to other pixel-based techniques (e.g., artificial neural networks) 14 which may not be able to find such optimal hyperplanes. Table 4.…”
Section: Classification Accuracy Assessmentmentioning
confidence: 99%
“…The overall result showed that SVM classification approach employed has got very promising potential to discriminate various soil salinity severity classes, with high classification accuracies, when combined with high spectral resolution hyperspectral remote sensing data. The overall high accuracy produced by the SVM classifier may be attributed to the ability of the algorithm to identify the optimally separating hyperplanes for classes in comparison to other pixel-based techniques (e.g., artificial neural networks) (Licciardi, et al, 2009) which may not be able to find such optimal hyperplanes. SVMs are also able to generalize this optimal separating hyperplane to unseen samples with the least errors among all separating hyperplanes.…”
Section: Accuracy Assessmentmentioning
confidence: 99%